Rozwijanie „kultury konfliktu” wśród dzieci - Cywińska , Małgorzata (Studia Edukacyjne, 2024)
This article aims to explore the constructive resolution of interpersonal conflicts, with a particular focus on childhood. It highlights the necessity for “conflict education” and the cultivation of a “culture of conflict” from early stages of life, emphasizing the importance of developing appropriate competencies during childhood for harmoniously resolving both personal and interpersonal conflicts. These are especially emotional-social and cognitive skills as well as problem-solving abilities. Well-designed programs for fostering constructive conflict resolution among children, along with specific methods and heuristic techniques, facilitate the development of a range of these competencies in children.